مدى إمكانية تفعيل الدائرة الدستورية في القضاء الليبي (بين القبول والرفض) - الاحرش أم كلثوم الجيلاني العربي (Sharwes Scientific Journal, 2024)
After the fall of the previous political regime in Libya, the three authorities (legislative-executive-judicial) were unable to manage and make public policies for the state, which would contribute to building the state, which led to a series of security and judicial challenges, due to the lack of agreement between the conflicting political forces over... Authority and this hinders the formulation of comprehensive national policy. Consolidating the values ​​of justice, human rights, and the principle of separation of the three powers. With the inability of the legislative authorities to carry out their work, the armed groups filled the gaps and deficits, sought to achieve their own goals and interests outside the law, and began ruling the country and performing the work of state institutions. They became responsible for managing the affairs of the state, and with a desire to survive and protect their interests, this led to the disruption of many Sensitive institutions, such as the Constitutional Chamber and the Land Registry, to prevent manipulation of state institutions and its citizens, and thus the transition from the legitimate state to the state of rights and law remains, where the rulers and the ruled are subject to the authority of the law. Hence, the most important challenges facing the formulation and management of public policy emerged. These challenges are numerous and intertwined and cannot be solved without a strong and effective will on the part of the political forces, by abolishing the parallel powers of the three authorities, bypassing individual, tribal and regional differences and interests, and building on a democratic and consensual basis that serves the public interest. The Constitutional Court in particular has been closed. In 2016 due to fears of politicization of its decisions, it will return to resume its duties in 2022. There must be a popular movement to change the fate of the country.